Marathon penguins – Reasons and consequences of long-range dispersal in Fiordland penguins / Tawaki during the pre-moult period - Mattern, Thomas; Pütz, Klemens; Garcia-Borboroglu, Pablo; Ellenberg, Ursula; Houston, David M.; Long, Robin; Lüthi, Benno; Seddon, Philip J. (PLOS ONE, 2018)
Migratory species often roam vast distances bringing them into contact with diverse conditions and threats that could play significant roles in their population dynamics. This is especially true if long-range travels occur within crucial stages of a species’ annual life-cycle. Crested penguins, for example, usually disperse over several hundreds of kilometres after completing the energetically demanding breeding season and in preparation for the costly annual moult. A basic understanding of crested penguins’ pre-moult dispersal is therefore paramount in order to be able to assess factors affecting individual survival. The Fiordland penguin, or Tawaki, the only crested penguin species breeding on the New Zealand mainland, is currently one of the least studied and rarest penguin species in the world. We successfully satellite tracked the pre-moult dispersal of 17 adult Tawaki from a single colony located in the species’ northern breeding distribution. Over the course of 8–10 weeks the penguins travelled up to 2,500 km away from their breeding colony, covering total swimming distances of up to 6,800 km. During outbound travels all penguins headed south-west within a well-defined corridor before branching out towards two general trip destinations. Birds leaving in late November travelled towards the Subtropical Front some 800 km south of Tasmania, whereas penguins that left in December headed further towards the subantarctic front. Using K-select analysis we examined the influence of oceanographic factors on the penguins’ dispersal. Water depth, surface current velocity and sea level anomalies had the greatest influence on penguin movements at the subantarctic Front, while sea surface temperature and chlorophyll a concentration were key for birds travelling to the subtropical front. We discuss our findings in the light of anthropogenic activities (or lack thereof) in the regions visited by the penguins as well as the potential consequences of Tawaki pre-moult dispersal for the species’ breeding distribution on the New Zealand mainland.